The Effect of Self Efficacy and Job Engagement on Job Insecurity Mediated By Employee Job Insecurity at Yogyakarta Branch Dazzle Store - Siti Yunisa (Journal Research of Social Science, Economics, and Management, 2022)
Challenges in today's globalization era are increasingly felt. The business aspect has a very high challenge to always be able to develop the company so that it is always profitable. The pandemic that hit from the beginning of 2020 has almost changed all existing business arrangements, including the aspect of human resource management. Employee job satisfaction is an important aspect for the company. Dazzle Store Yogyakarta Branch is a retail company engaged in marketing electronic goods with international brands. This study aims to determine the direct and indirect effect of self-efficacy and job engagement on job satisfaction through job insecurity for employees of Dazzle Store Yogyakarta branch.